An approach to reduce turn around timeand waiting timeby the selection of round robin and shortest job first algorithm - Kumar, Sarvesh; Kumar, Gaurav; Jain, Komal; Jain, Aditi (International Journal of Engineering and Technology, 2018)
In this research, a study on operating system tells about its working,  how it helps as interface between user software and system  hardware .To implement this, different scheduling is used to provide multiple processing in a hardware. There are different levels of scheduler applied in different levels of process from ready queue to termination. This paper focuses on the average amount of waiting time and amount of turnaround time of processes. The proposed algorithm purely defines less waiting time and turnaround time as compared to the round robin scheduling and shortest job first scheduling algorithm.
Keywords: Round Robin Scheduling; Shortest Job First; Scheduler; Operating System; Turnaround Time; Waiting Time